In Memoriam: Ali Ozden (1942-2020) - Yurdaydın, Cihan; Ertan, Atilla (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Yurdaydın C, Ertan A. In Memoriam: Ali Ozden (1942-2020). Turk J Gastroenterol 2020; 31(11): 734.